Cyclodextrin inclusion complexes enhance the solubility and anti-virulence activity of metronidazole against uropathogenic Proteus mirabilis - Rehab Mahmoud Abd El-Baky; Zeinab Fathalla; Hala Rady Ahmed; Ramadan Yahia; Mohamed A. Mawhoup; Ghada M. Sadiq; Hebatallah S. Barakat; Adel Al Fatease; Ali H. Alamri; Hamdy Abdelkader (PLoS ONE, 2026)
Proteus mirabilis is a major uropathogen implicated in catheter-associated urinary tract infections and infection-induced urolithiasis, often exhibiting multidrug resistance. Improving the solubility and bioactivity of existing drugs represents a promising pharmaceutical strategy to overcome these challenges. In this study, inclusion complexes of metronidazole with α-cyclodextrin (α-CD), β-cyclodextrin (β-CD), and hydroxypropyl-β-cyclodextrin (HP-β-CD) were prepared using physical mixing and kneading methods. Complexes were characterized using differential scanning calorimetry (DSC) and Fourier-transform infrared spectroscopy (FTIR). In vitro release behaviour, minimum inhibitory concentration (MIC), and effects at sub-MIC levels on motility, urease-associated phenotype, and biofilm formation were evaluated. β-CD and HP-β-CD systems demonstrated improved release profiles compared to metronidazole alone. While MIC values remained within the mg/mL range, HP-β-CD complexes showed reduced MIC relative to aqueous metronidazole, achieving a four-fold reduction in MIC. At sub-MIC concentrations, β-CD and HP-β-CD formulations were associated with significant suppression of motility, reduced urease-associated phenotypes, and inhibition of biofilm formation. Molecular docking suggested spatial compatibility between metronidazole and cyclodextrins, though mechanistic conclusions remain predictive. These findings indicate that cyclodextrin-based complexation enhances physicochemical performance of metronidazole and may support adjunctive anti-virulence modulation in P. mirabilis. Further mechanistic and in-vivo studies are required to validate translational relevance.